Textile fabrics abrasion resistance – The instrumental method for end point assessment - Jasińska Izabela (AUTEX Research Journal)
Determination of abrasion resistance of textile fabrics is one of the important parameters describing textile durability, especially utility properties. Currently, used test methods for determination of abrasion resistance are based on organoleptic examination. The end point of the abrasion resistance test carried out for textile fabrics is described in the form of criteria in the standard. The identification of the end point requires manual observation of the sample’s surface. This process is labour and time-consuming and requires a lot of experience. The article presented a new instrumental method for assessing abrasion resistance. The method, based on image analysis techniques, allows identifying the end point of abrasion test without a constant examination of sample surface, without constantly examining the sample surface. The method presented for abrasion resistance assessment involves evaluation of brightness profiles taken from sample scans. The new method, subjected to precision experiments, has shown a good level of repeatability and reproducibility. The instrumental method, together with end point criteria for single thread, could support operators during breakage identification test significantly, shortening the test time and labour consumption.